Hubungan Power Otot Lengan dan Koordinasi Mata Tangan terhadap Hasil Pukulan Groundstroke Backhand Tenis Lapangan pada Mahasiswa Pendidikan Jasmani Universitas Tanjungpura - Lukito, Dimar Jati; Hidasari, Fitriana Puspa; Suwanto, Witri; Yunitaningrum, Wiwik; Bafadal, Muhammad Fachrurrozi (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2024)
This study aims to determine the relationship between arm muscle power and hand eye coordination on backhand groundstrokes in Physical Education students at Tanjungpura University. This research uses quantitative methods with a correlational approach. Based on statistical analysis, it was found that there is a correlation between arm muscle power and backhand groundstrokes, this can be seen from the results of the product moment correlation test rx_1y which was obtained, namely 0.683, a significant relationship can be seen from the obtained value of r calculated = 0.683 > r table = 0.632, and There is also a significant relationship between eye-hand coordination and backhand groundstrokes, this can be seen from the results of the product moment correlation test rx_2y which was obtained at 0.744, therefore there is a very significant relationship as seen from the obtained value of r calculated = 0.744 > r table = 0.632 . After the results x_1Y and x_2Y are obtained, they are tested again using the multiple correlation test, which is useful for getting how big the correlation is. The results of the research show that arm muscle power and eye-hand coordination have coefficient values for backhand groundstrokes, this can be seen from the results of the multiple correlation test obtained which is 0.81. If the calculation results are seen from the r value interpretation table, then a value of 0.81 indicates a high correlation category. Keywords: Hand Eye Coordination, Arm Muscle Power, Backhand Groundstroke